ANALISIS TINGKAT KESEJAHTERAAN RUMAH TANGGA NELAYAN - Yahya, Kholid; Pudjihardjo, M. (Journal of Development Economic and Social Studies, 2024)
The study was conducted on a fisherman's household in Weru Village, Paciran district of Lamongan. The objective of the study was to find out the relationship between income, consumption, housing conditions, accommodation facilities, family members' health, access to health services, children's access to education, and access to transport facilities to the well-being of fishermen's households, both simultaneously and partially. The method used in this research uses associative descriptive methods. The study used 91 as a sample of the study using double linear regression analysis. Hypothesis testing in this study uses test-F and test-t statistics. The statistical analytics process uses the SPSS for Windows 25 program. According to the results of the study, the influence of income, consumption, housing conditions, accommodation facilities, the health of family members, access to health services, children's education, and access to transport facilities on the well-being of fishermen's households, carried out with a determination coefficient analysis, has an impact of 0.998 or 99.8%, i.e. income, consumer, conditions of housing, accommodations, family members' health, health of health services access, child education access, and transport facility access have an effect of 99.8% on fisherman's welfare and the remaining 0.2% is influenced by other factors not studied by the author.